Discovery of two neighboring satellites in the Carina constellation with MagLiteS - Torrealba, Gabriel; Martin, Nicolas F.; Martínez-Delgado, David; Noël, Noelia E. D. (Arxiv, 2018)
We report the discovery of two ultra-faint satellites in the vicinity of the Large Magellanic Cloud (LMC) in data from the Magellanic Satellites Survey (MagLiteS). Situated 18$^{°}$ ($\sim 20$ kpc) from the LMC and separated from each other by only $18^′$, Carina~II and III form an intriguing pair. By simultaneously modeling the spatial and the color-magnitude stellar distributions, we find that both Carina~II and Carina~III are likely dwarf galaxies, although this is less clear for Carina~III. There are in fact several obvious differences between the two satellites. While both are well described by an old and metal poor population, Carina~II is located at $\sim 36$ kpc from the Sun, with $M_V\sim-4.5$ and $r_h\sim 90$ pc, and it is further confirmed by the discovery of 3 RR Lyrae at the right distance. In contrast, Carina~III is much more elongated, measured to be fainter ($M_V\sim-2.4$), significantly more compact ($r_h\sim30$ pc), and closer to the Sun, at $\sim 28$ kpc, placing it only 8 kpc away from Car~II. Together with several other systems detected by the Dark Energy Camera, Carina~II and III form a strongly anisotropic cloud of satellites in the vicinity of the Magellanic Clouds.
Gesehen am 14.03.2018